Guernica, Lorca and the 1939-1945 test: The Spanish Civil War in Portuguese textbooks - Neto, Sérgio; Serrano, Clara Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to study how the Spanish Civil War has been approached by Portuguese 9th-grade History textbooks, from the 80s until nowadays. Using a qualitative-comparative methodology, we analyse topics such as the number of pages and quantity/quality of information; historical documents used; relation with other historical contents, among others. From this analysis, it is concluded that, despite the historical relevance and the geographic and temporal proximity of the theme, it has been taught in an increasingly brief, almost schematic way, with little problematisation of the content.